2014
DOI: 10.1179/2045772314y.0000000236
|View full text |Cite
|
Sign up to set email alerts
|

Chronic activity-based therapy does not improve body composition, insulin-like growth factor-I, adiponectin, or myostatin in persons with spinal cord injury

Abstract: Spinal cord injury (SCI) induces dramatic changes in body composition including reductions in fat-free mass (FFM) and increases in fat mass (FM). Objective: To examine changes in body composition in response to chronic activity-based therapy (ABT) in persons with SCI. Design: Longitudinal exercise intervention. Methods: Seventeen men and women with SCI (mean age = 36.1 ± 11.5 years) completed 6 months of supervised ABT consisting of load bearing, resistance training, locomotor training, and functional electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…Bakkum et al, (2015) found no beneficial effects of hybrid functional electrical stimulation leg cycling in comparison to arm cycling alone on visceral adiposity, although improvements in metabolic and body composition outcomes have been noted in other similar training interventions (Gorgey et al, 2012, Griffin et al, 2009. Other novel exercise rehabilitation interventions, such as activity-based therapy have also shown limited effects on trunk fat (Astorino et al 2014), although few studies have examined VAT specifically. The potential causal relationship between LTPA and VAT should be further investigated in a prospective training study using a supervised, progressive training program meeting current population-specific guidelines for physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bakkum et al, (2015) found no beneficial effects of hybrid functional electrical stimulation leg cycling in comparison to arm cycling alone on visceral adiposity, although improvements in metabolic and body composition outcomes have been noted in other similar training interventions (Gorgey et al, 2012, Griffin et al, 2009. Other novel exercise rehabilitation interventions, such as activity-based therapy have also shown limited effects on trunk fat (Astorino et al 2014), although few studies have examined VAT specifically. The potential causal relationship between LTPA and VAT should be further investigated in a prospective training study using a supervised, progressive training program meeting current population-specific guidelines for physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…There are few related studies available and a recent trial indicates no change in myostatin and IGF-I, as well as in body weight, among patients with SCI after chronic exercise training [ 21 ]. In contrast to the aerobic training by arm ergometry in this study, the cited trial used activity-based training that mainly consisted of resistance and locomotor training focused on the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are limited studies that explore the changes of serum myokines after chronic exercise training in patients with SCI. Only one small trial indicated no significant changes of serum myokines after activity-based training [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, with exception of arm ergometry and FES, these modalities are typically expensive and localized to a few specialized facilities. They also require many trained personnel to operate equipment and/or monitor training, and many months of training tend to elicit relatively small gains in variables including bone mineral density [ 16 ] and body composition [ 17 ] which are dramatically altered after SCI and thus commonly identified as targets of rehabilitation to improve health status. So despite the documented success of exercise-based rehabilitation in promoting health-based outcomes, it may be somewhat impractical for most persons with long-term SCI to access.…”
Section: Introductionmentioning
confidence: 99%